Allograft and patient survival after sequential HSCT and kidney transplantation from the same donor—A multicenter analysis. Issue 2 (13th July 2018) - Eder, Michael; Schwarz, Christoph; Kammer, Michael; Jacobsen, Niels; Stavroula, Masouridi Levrat; Cowan, Morton J.; Chongkrairatanakul, Tepsiri; Gaston, Robert; Ravanan, Rommel; Ishida, Hideki; Bachmann, Anette; Alvarez, Sergio; et al.
Abstract : Tolerance induction through simultaneous hematopoietic stem cell and renal transplantation has shown promising results, but it is hampered by the toxicity of preconditioning therapies and graft‐versus‐host disease (GVHD). Moreover, renal function has never been compared to conventionally transplanted patients, thus, whether donor‐specific tolerance results in improved outcomes remains unanswered. We collected follow‐up data of published cases of renal transplantations after hematopoietic stem cell transplantation from the same donor and compared patient and transplant kidney survival as well as function with caliper‐matched living‐donor renal transplantations from the Austrian dialysis and transplant registry. Overall, 22 tolerant and 20 control patients were included (median observation period 10 years [range 11 months to 26 years]). In the tolerant group, no renal allograft loss was reported, whereas 3 were lost in the control group. Median creatinine levels were 85 μmol/l (interquartile range [IQR] 72‐99) in the tolerant cohort and 118 μmol/l (IQR 99‐143) in the control group. Mixed linear‐model showed around 29% lower average creatinine levels throughout follow‐up in the tolerant group ( P < .01). Our data clearly show stable renal graft function without long‐term immunosuppression for many years, suggesting permanent donor‐specific tolerance. Thus sequential transplantation might be an alternative approach for future studies targeting tolerance induction in renal allograft recipients. Abstract : A long‐term follow‐up analysis shows stable renal graft function without immunosuppression and no graft loss in patients receiving renal transplantation after hematopoietic stem cell transplantation from the same donor.